Controllable enormous valley splitting in Janus WSSe on CrN monolayer. (4th August 2021) - Tang, Weiqing; Wu, Xuefeng; Wu, Yaping; Wu, Zhiming; Shuping, Li; Kang, Junyong
Abstract: Manipulation of valley polarization in low-dimensional systems is desirable for future applications in information process and storage. Here, we design two-dimensional WSSe / CrN van der Waals heterostructures and control the valley degree of freedom based on the first-principles calculations. Combining the internal electric field and magnetic proximity effect, the interfacial interaction and the valley splitting are efficiently modulated in the system. Intrinsic enormous valley splitting of 103 meV and 144 meV are generated in S- and Se-terminated WSSe/CrN heterostructures, which corresponds to the effective Zeeman magnetic field of 1280 and 1574 T, respectively. A prominent anomalous Hall conductivity at K valley is induced by time-reversal symmetry breaking and sizable Berry curvature. Furthermore, valley splitting can be manipulated continually by the in-plane strain and interlayer distance. The largest valley splitting of 272 (240) meV and the effective Zeeman magnetic field of 2560 (2275) T are achieved for S (Se)-terminated WSSe/CrN heterostructures, respectively, under the compressive interlayer distance. It is found that the changes of induced spin charges around S and W atom are responsible for the modulated valley splitting. This work opens new vistas for the design of valleytronic devices.